Избранное - Блок Александр Александрович (Школа классики, 2001)
Экземпляры: аб. (2001) / Инвентарный номер: 43564 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Б 70 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5